Greenwashing and its influence on fast fashion consumption - Müller Pérez, Jessica; Hernández Pérez, Luis Manuel (RAN - Revista Academia & Negocios, 2025)
Purpose: To analyze the purchasing intention of sustainable fashion among Mexican women according to the Theory of Planned Behavior (TPB), incorporating greenwashing, perceived risk, and aesthetic risk as additional variables. Methodology: A structural equation model (SEM) was estimated. Data collection was conducted through an online survey, targeting Mexican women who consume fashion products. Results: The variable subjective norms acted as the main determinant of sustainable purchasing intentions, followed by attitudes. The variables economic risk, aesthetic risk, and perception of greenwashing were statistically significant, contributing to the adequacy and validity of the proposed model. Implications: Subjective norms and attitudes are key factors influencing responsible purchasing intentions, which support and expand the applicability of the TPB in sustainable consumption contexts. Messages associated with sustainability should be strengthened through close role models (family, friends, local influencers), emphasizing the connection of sustainable fashion with personal benefits, lifestyle aspirations, and emotional values, beyond rational or informative arguments. Originality: The incorporation of greenwashing perceptions as an explanatory variable within the model constitutes a novel contribution, as it opens new lines of research on the role of perceived authenticity and brand trust in green purchasing intentions, especially among younger consumers.